2012
DOI: 10.1039/c2ob25299f
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic influence of the substitution of alkylidene-5H-furan-2-ones in Diels–Alder cycloadditions with o-quinonedimethide as diene partner: en route to the CDEF polycyclic ring system of lactonamycin

Abstract: An efficient and rapid synthesis of the CDEF ring system of lactonamycinone is reported via a highly chemo- and diastereoselective intermolecular Diels-Alder cycloaddition between trans-1,2-disilyloxybenzocyclobutene and the appropriate γ-alkylidenebutenolide. The feasibility and the total chemoselectivity of the [4 + 2] cycloaddition for the construction of a spirolactone moiety via an intramolecular approach (IMDA) using both partners is also described demonstrating the versatility of the γ-alkylidenebutenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…[64] In view of their promising biological activities and complex architectures involving a densely oxygenated furo [3,2-b]furanone motif fused with an unusual naphtha[e]isoindole ring system, lactonamycins stimulated many synthetic studies, especially directed at the aglycon lactonamycinone (203). [65]…”
Section: Lactonamycin (14)mentioning
confidence: 99%
“…[64] In view of their promising biological activities and complex architectures involving a densely oxygenated furo [3,2-b]furanone motif fused with an unusual naphtha[e]isoindole ring system, lactonamycins stimulated many synthetic studies, especially directed at the aglycon lactonamycinone (203). [65]…”
Section: Lactonamycin (14)mentioning
confidence: 99%
“…15 Concerning note number 15, in which a comment is made on the level of calculation we used, we shall mention the following points. First of all, it is interesting to note that in the studies of Korth et al 3 the authors have used the semi empirical PM3 method that is, to date, unambiguously not reliable for a such study. Secondly, we did a careful benchmark of some functionals against CCSD(T)/def2-QZVP, which was recently published in the opening of benzocyclobutene derivatives (P. Nava and Y. Carissan, Phys.…”
Section: Rtmentioning
confidence: 99%
“…Because cycloaddition reactions are among the most useful processes for generating molecular complexity, inter-and intramolecular [4+2]-cycloaddition reactions between trans-1,2disiloxybenzocyclobutenes 1 and d-substituted g-alkylidenebutenolides 2 yielded, under very mild conditions, these spirolactone moieties 3 or naphthofuranone moieties 4 and, at least, gave an access to deoxylambertellol B 5 3 and the CDEF ring system of lactonamycinone 6 (Scheme 1). 4 During these studies, we observed that trans-1,2-disiloxybenzocyclobutene 1 was very reactive towards the dioxygen, even without any activation, giving the corresponding endo-peroxide 7 which has been detected during both preparation of 1 (reduction of diketone 8 followed by protection of the hydroxyl function) and in subsequent [4+2]-cycloaddition reaction. Particularly, we found that the use of oxygen free solvents under strictly inert Ar atmosphere was a crucial point to obtain good yields in the preparation of 3 or 4.…”
Section: Introductionmentioning
confidence: 96%